Recent Advances in Biodegradable Magnesium Alloys for Medical Implants: Evolution, Innovations, and Clinical Translation - Aikin, M.; Shalomeev, V.; Kukhar, V. V.; Kostryzhev, A.; Kuziev, I.; Kulynych, V.; Dykha, O.; Dytyniuk, V.; Shapoval, O.; Zagorskis, A.; Burko, V.; Khliestova, O.; et al. (MDPI, 2025)
Biodegradable magnesium alloys have emerged as promising alternatives to permanent metallic implants due to their unique combination of mechanical compatibility with bone and complete resorption, addressing the persistent issues of stress shielding and secondary removal surgeries. This review critically examines the historical development of magnesium-based biomaterials, highlighting advances in alloy design, manufacturing processes, and surface engineering that now enable tailored degradation and improved clinical performance. Drawing on recent clinical and preclinical studies, we summarize improvements in corrosion resistance, mechanical properties, and biocompatibility that have supported the clinical translation of magnesium alloys across a variety of orthopedic and emerging medical applications. However, challenges remain, including unpredictable in vivo degradation kinetics, limited long-term safety data, lack of standardized testing protocols, and ongoing regulatory uncertainties. We conclude that while magnesiumbased biomaterials have advanced from experimental concepts to clinically validated solutions, further progress in personalized degradation control, real-time monitoring, and harmonized regulatory frameworks is needed to fully realize their transformative clinical potential.
Keywords: biodegradable magnesium alloys; orthopedic implants; corrosion resistance; surface engineering; clinical translation; rare-earth-free alloys; additive manufacturing; regulatory challenges; biocompatibility; smart medical devices